Dietary fibre and the prevention of chronic disease – should health professionals be doing more to raise awareness?. Issue 3 (13th May 2016) - Lockyer, S.; Spiro, A.; Stanner, S.
Abstract: The recent report on Carbohydrates and Health by the Scientific Advisory Committee on Nutrition concluded that a high fibre intake is associated with reduced risk of a number of significant chronic diseases in the UK, although further studies are needed to fully elucidate the precise mechanisms involved. New recommendations have been set for adults and younger people but dietary surveys suggest that intakes are currently well below these targets, reflecting low consumption of fibre‐containing foods such as fruit, vegetables, nuts and seeds and high‐fibre/wholegrain starchy foods. A wide number of interrelated barriers to increasing intakes have been purported. These include a lack of awareness of the health benefits of fibre; relatively little interest amongst the media compared with other nutrients ( e.g . sugars); perceived high cost of fruit and vegetables; perceptions of starchy carbohydrates as unhealthy; taste preferences for refined grains; lack of a specific dietary recommendation or national awareness campaign for fibre or wholegrain intake; no general permitted (European Food Safety Authority approved) health claims for fibre and wholegrain; and a lack of mandatory labelling of fibre values on packaging. Health professionals have an important role in giving dietary advice, including the promotion of dietary fibre. However, as well as limited time during appointments to discuss diet and lifestyle issues, the level of confidence and competency in delivering such advice may be lacking amongst some health professionals. Current knowledge and awareness of the key messages around dietary fibre amongst health professionals have been poorly studied. A small online survey of UK practice nurses ( n  =   50) recently commissioned by the British Nutrition Foundation suggested that, although the benefits of dietary fibre intake in relation to cardiovascular disease, type 2 diabetes and colorectal cancer are largely acknowledged, the perceived importance of fibre for patient health is lower than other nutrients such as fat and sugars. One in five nurses reported not having adequate skills or knowledge to offer dietary advice and one in four said they sometimes lacked the confidence to give dietary advice to their patients. In view of the evidence for the health benefits for dietary fibre, there is a need to increase the importance that health professionals place on communicating ways to boost intakes amongst their patients. Easy to access nutrition training for health professionals would help to support this objective.